Gender theory as a factor of formation of gender competency in the process of cultural education of students - Slobodianiuk, O. M. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The article deals with the theory of gender as a factor of gender competence formation in the process of cultural education of students. The main conclusion of the paper is that in modern Ukrainian society the actual formation of gender competence of students is corresponding to an egalitarian gender culture of the type of society, because the basis of gender identity is gender competence, actual content of which depends on the regulatory value orientations of the dominant society in gender culture.